An Active-Learning Framework for Educating Medical Students on SARS-CoV-2 Variants and COVID-19 Epidemiology [version 1; peer review: 2 approved] - Samiksha Prasad; Amanda J Chase (MedEdPublish)
Background The emergence of multiple Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) variants presented an escalated risk to public health globally and prompted epidemiologic monitoring and classification. Health professionals are vital for patient education regarding Coronavirus Disease 2019 (COVID-19), discussing patient concerns, and providing guidance. Students enrolled in professional healthcare programs benefit from being adept with the evolution and spread of SARS-CoV-2 variants, and a team-based learning module can be helpful for applying foundational concepts to clinical problems. Methods This team-based learning (TBL) framework was developed in response to the COVID-19 pandemic and the emergence of viral variants. It was placed at the end of a hematology block within the first semester of year one of the medical school during the academic years 2021–2022. It consists of a 7-question readiness assurance process and a four-question application exercise. Results The average score increased from 58.8% (iRAT) to 85.9% (tRAT) (n=104). The post-session survey data showed an increase in students’ understanding of the classification of COVID-19 variants and the role of genetic mutations in viral pathogenesis. Qualitative data yielded positive feedback for the session, notably in students' ability to interpret phylogenetic trees and understand the role of variants. Conclusions This TBL framework cultivates higher-order thinking skills among medical students and effectively integrates virology, epidemiology, and pathology. Additionally, it provides a framework for developing a robust and up-to-date platform for the discussion of novel variants of COVID-19 or other infectious diseases.